PENGARUH DUKUNGAN KELUARGA TERHADAP KEBERFUNGSIAN SOSIAL ORANG DENGAN HIV/AIDS (ODHA) DI RUMAH SINGGAH CARITAS PSE MEDAN - Henny Kristian Siboro (Welfare StatE, 2013)
People with HIV / AIDS are infected with the HIV virus in the body, most individuals with HIV / AIDS is more easily discriminated and stigmatized in society. So that people with HIV / AIDS have a problem not only on the physical but also psychological, then it need by treatment and mental health recovery. On mental recovery or soul family support is a very important thing needed by people with HIV / AIDS. So that people with HIV are fully supported by both families of everything can improve or restore the social functioning of people with HIV / AIDS themselves. The research was conducted at Caritas Shelter Home PSE Field which is an organization engaged in the issue of HIV / AIDS and Narcotics. Handling a socialized understanding of HIV / AIDS transmission and prevention by way of direct visits to the hospital that specialized care for people with HIV or come directly to the house to meet clients or their families (family based), and provide information about therapy ARV treatment (Anti-Retroviral). This research is explanatory research that aims to examine the relationship between the study variables and test hypotheses that have been formulated previously. Variables in this study consists of the independent variable (x) is a family support and the dependent variable (y) the social functioning of people with HIV / AIDS. Based on the calculation of Spearman rank correlation coefficient, it can be seen that the correlation between X and Y with N = 50 obtained a value of 0.67. Results of data analysis showed that the effect of family support has a positive relationship to social functioning steady person with HIV / AIDS (PHAs). Based on the research I have done if there are many families who do not understand well about HIV / AIDS so that there should be an institution that approaches to tackle the issue of HIV / AIDS, in order to be disseminated to families living both urban and rural areas. Keywords: Effects , Family Support , social functioning , people with HIV / AIDS